2022
DOI: 10.1186/s12913-022-08087-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with health care at a tertiary hospital in Northern Malawi: results from a triangulated cross-sectional study

Abstract: Background In 2016 the Malawi government embarked on several interrelated health sector reforms aimed at improving the quality of health services at all levels of care and attain Universal Health Coverage by 2030. Patient satisfaction with services is an important proxy measure of quality. We assessed patient satisfaction at a tertiary hospital in Northern Malawi to understand the current state. Methods We conducted exit interviews with patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Medical/health background is a predictor to quality of hospital care. A recently published paper found significant predictor of occupation to healthcare services in hospitals 30. Those subgroups are familiar to their colleagues working in hospitals thus health professionals, especially nurses and physicians; treat them carefully with respect, dignity and showing extreme attention and care.…”
Section: Discussionmentioning
confidence: 98%
“…Medical/health background is a predictor to quality of hospital care. A recently published paper found significant predictor of occupation to healthcare services in hospitals 30. Those subgroups are familiar to their colleagues working in hospitals thus health professionals, especially nurses and physicians; treat them carefully with respect, dignity and showing extreme attention and care.…”
Section: Discussionmentioning
confidence: 98%
“…Patient satisfaction reflects the alignment between patient expectations and the care they receive but has limitations in measuring care quality. It encompasses factors like provider availability, cost, and facility environment, directly linked to service quality [1]. Determinants of patient satisfaction encompass healthcare provider traits, socio-psychological factors, health and socioeconomic status, and demographics.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized as a crucial indicator of care quality in hospitals across many countries. Hospitals can use patient-specific satisfaction metric to identify areas for improvement, ultimately enhancing the patient experience and clinical outcomes [7] . Previous studies have shown that higher satisfaction is associated with persistence, compliance, self-care behavior effectiveness, and improved prognosis [8][9] .…”
Section: Introductionmentioning
confidence: 99%